Social capital and innovation: an empirical analysis in the context of European regions - Jose M Barrutia; Carmen Echebarria; Ainhize Gilsanz (European Regional Science Association (ERSA), 2010)
Although conceptual support for the relevance of social capital as an antecedent of innovation has received much theoretical attention over recent years, measurement and quantitative evidence are scarce, particularly in regional contexts. Available empirical research referring to different units of analysis (individuals, organizations, and so on) supports, in general terms, a linear positive relationship among some components of social capital and innovation. Yet some studies also offer controversial results by finding non-significant, negative, diminishing returns and quadratic relationships. Building on the social network theory of innovation, this paper seeks to contribute some insights to this stream of research by empirically testing the impact of social capital on innovation in 54 NUTS1 European regions. Our results show that the social capital-innovation relationship has an inverted U-shape, which is consistent with recent research that suggests that some sub-constructs of social capital, such as tie strength, involve maintenance and opportunity costs and that social capital has positive effects but has also its limits.
Keywords: 330; Innovation; social capital; European regions; intellectual capital; learning